HOOLIGAN: BARCLAYS PREMIER LEAGUE: A CULTURAL DISCOURSE ANALYSIS - Nugroho, Bagus Indro; Ricahyono, Sigit (English Teaching Journal, 2014)
Culture or history of each club in Barclays Premiere League and its hooligan influence the name of hooligan. The purposes of this study is identifying linguistics form of the Hooligan Firmâs name in football club of Barclays Premiere League and is analyzing how the socio-cultural contexts relates to the Hooligan Firmâs name in football club of Barclays Premiere League. This research uses Cultural Discourse Analysis (CuDA) as the grand design of analytical framework. CuDA concerns with analyzing of the impact of the culture to language. The type of qualitative method for this research are content analysis and documentation is used to collect the data. The results of this research shows the linguistic forms of Hooligan Firmâs name are constructed by words, leading to nouns by inflectionalÂ  andÂ  derivationalÂ  suffixes, Â andÂ  phrases,Â  leading to Â Head Â andÂ  Modifier.Â  The cultural background of Hooligan Firmâs name comes from the nickname of the club, the police rules, and the social conditions of the members. It deals with the matter of masculinity to get power among others.